Enhancement of neural cell regeneration and survival by altering gap junctional communication following brain injury - Morin, Mario Y (University of Ottawa (Canada), 2006)
The adult brain is particularly susceptible to injury given that it lacks significant regenerative capacity. The presence of rare neural stem and progenitor cells - cells capable of self-renewal and specification to a neuronal or a glial lineage - in specific areas of the adult central nervous system (CNS) offers new hope for therapeutic cell replacement. Our laboratory has previously implicated connexin32 (Cx32) in participating in neural progenitor cell fate determination to an oligodendrocyte lineage (Melanson-Drapeau et al., 2003; Hebb et al., submitted). Based on these previous findings, I hypothesized that neuronal regeneration might be increased in Cx32 knockout (KO) mice following hippocampal injury. Kainic acid (KA)-induced epileptic seizure was used to elicit loss of hippocampal neurons and study subsequent progenitor cell proliferation and specification to neurons and oligodendrocytes in the hippocampus of adult wild type (WT) and Cx32KO mice. The kinetics of hippocampal cellular degeneration and regeneration were established following seizure by qualitative and quantitative histological analyses. I found that the viability of the granule cell population in the dentate gyrus (DG) was compromised following excitotoxic challenge but that damaged cells recovered four weeks post-injury without undergoing significant cell death. Substantial neuronal loss with both apoptotic and non-apoptotic characteristics was detected in the CA3 field of the hippocampus 0.5 weeks post-injury in both genotypes. Significant progenitor cell amplification (proliferation) was observed in the CA3 field at the same time period. Progenitor cells in Cx32KO mice preferentially committed to a neuronal lineage, increasing neuroregeneration 4.5 weeks following injury. The Morris water maze, a hippocampal dependent spatial memory task, was used to test the functionality of these new neurons four weeks following KA-induced injury. I show that uninjured WT and Cx32KO mice exhibit comparable indices of spatial learning and memory. Following KA-induced seizure, WT mice are behaviourally impaired while Cx32KO mice are not, providing strong evidence of enhanced functional neuroregeneration in the absence of Cx32. Finally, to provide a tool to track the fate of neural progenitors destined to express Cx32 over time following injury, a new transgenic marker mouse, that expresses the enhanced green fluorescent protein (EGFP) in place of Cx32, was engineered for use in future studies.
Keywords: Biology, Neuroscience.; Chemistry, Biochemistry.